Strategies to Enhance TVET Students' Participation in the Malaysian Construction Industry - Suffian, Khairun Najwa; Mohamed Aris, Nur Arzwin; Zainal, Nuratiqah; Mohamed @ Jamal, Abidah Ainah (Journal of Technology Management and Business, 2026)
The construction sector is one of the key contributors to Malaysia’s economic development and infrastructure. However, the participation of Technical and Vocational Education and Training (TVET) students in the construction industry remains low, despite the availability of numerous career opportunities. This issue is attributed to several factors, including negative perceptions of 3D jobs (Dirty, Dangerous, and Difficult), a mismatch between TVET training and industry requirements, and concerns about safety and career prospects. Therefore, this study is conducted to identify the factors that influence the participation of TVET students, examine the effectiveness of TVET training in providing the technical skills needed in the construction industry, and to propose improvement strategies to enhance their participation in the Malaysian construction industry. A quantitative approach was employed, using a questionnaire administered to 187 students from six vocational colleges in Johor offering construction-related programs. The analysis revealed that industry engagement through mentoring, structured training (dual learning), and curriculum updates with current technologies such as BIM and IBS enhance students’ confidence, technical skills, and employability. Continuous TVET promotion, family support, and active industry involvement proved to be the key strategies to attract students to the construction sector while developing a skilled and competitive local workforce. Strategic collaboration between TVET institutions, industry, and the government is essential to foster student interest in construction and build a competent local workforce.